Interaction of Hyperoside with Human Serum Albumin and Effect of Glucose on the Binding. (23rd July 2014) - Yang, Jie; Qu, Lingling; Yang, Wenyue; Huang, Yun; Jiao, Ning; Zhan, Wenhong; Zhao, Ding; Cui, Lijian
Abstract : The interaction of hyperoside (Hyp) with human serum albumin (HSA) and effect of glucose on the binding were studied in simulating physiological condition (pH 7.40). The results suggested that Hyp quenched the endogenous fluorescence of HSA via a static quenching process with the distance of 1.95 nm between Hyp and HSA. Hydrophobic forces played a major role in stabilizing the Hyp-HSA complex. Through synchronous fluorescence monitoring of conformation of HSA, we found that the binding to Hyp can change the microenvironment around tryptophan (Trp) residues. Increasing in glucose concentration over a range from 0 to 9 mM decreased the binding ability of HSA to Hyp, implying that increasing in glucose concentration would increase the concentration of free Hyp.